ANALISIS PENAWARAN DAN PERMINTAAN SERTA POTENSI EKSPOR DAGING BABI INDONESIA - I KETUT KARIYASA; NYAK ILHAM (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2002)
Supply and demand analysis model of pork meat in Indonesia, including thecapability of its export rate, using national time series data period 1975-1999.Thisanalysis is using econometrical approach with Ordinary Least Squares (OLS) method.The result shows that from supply side, price of meat itself, price of the pork, netimport of pork meat, and quantity population of pork influence it. From demandside, influenced by the price of its meat, price of fish, and income. In ten year ahead,the capability of export rate for pork meat will be large enough, and considered to be48,7% from production. This rate could be reached by improving quality of cattle andmeat, making conducive environment for investing and spreading out this cattlebusiness into large area, which support its environment living from many aspects,such as social, cultural, and religion aspect.